2008
DOI: 10.1016/s1875-9572(09)60016-4
|View full text |Cite
|
Sign up to set email alerts
|

The Perinatal Outcomes of Asymptomatic Isolated Single Umbilical Artery in Full-term Neonates

Abstract: SUA is a relatively rare finding. When a SUA is identified, the routine check of karyotyping and kidney sonography for possible chromosome and associated renal anomalies may be unnecessary. According to lighter placental weight probably causing the higher incidence of small for gestational age (SGA), pregnancies with isolated SUA should be carefully monitored for evidence of fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
1
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 10 publications
5
18
1
12
Order By: Relevance
“…The incidence in most studies is 0.2 to 1.6% (euploid) to 9 to 10% (anueploid pregnancies). 8 In our study the incidence was 0.88 per 100 pregnancies. SUA is associated with congenital anomalies.…”
Section: Discussionsupporting
confidence: 46%
“…The incidence in most studies is 0.2 to 1.6% (euploid) to 9 to 10% (anueploid pregnancies). 8 In our study the incidence was 0.88 per 100 pregnancies. SUA is associated with congenital anomalies.…”
Section: Discussionsupporting
confidence: 46%
“…Based on these findings, some authors have recommended that fetal growth should be monitored throughout pregnancy after prenatal diagnosis of a single umbilical artery. [7][8][9]11,12 As a matter of fact, throughout the study period, our management protocol for pregnancies diagnosed with ISUA included serial follow up fetal growth scans. And when fetal growth restriction was diagnosed additional fetal well being tests were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory mechanisms allow increase in blood flow through the single artery in order to meet the demands of fetal growth and development throughout pregnancy. 3 Although several studies have reported diminished fetal growth in these pregnancies, [4][5][6][7][8][9][10][11][12] others have not shown differences. [13][14][15] These contradictory findings may be attributed to diverse methodological differences in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal outcomes that have been evaluated previously in the literature include birthweight, gestational age at delivery, fetal anomalies, and neonatal intensive care unit admissions. 2,6,7 Although the association between antenatal ultrasound findings and birth outcomes has been evaluated, there have been no data regarding long-term outcomes in affected infants. Our study aims to identify whether there are any long-term implications of SUA on physical and neurologic development.…”
mentioning
confidence: 99%